Las conductas disruptivas y su incidencia en el rendimiento académico de los estudiantes de 9no año de Educación General Básica - Morán Donoso, Johanna Patricia (2020)
This research aims to determine the incidence of disruptive behaviors on the academic performance of students of the 9th Year of Basic General Education of the Educational Unit "Arnulfo Jaramillo Sierra", in which the presence of disruptive behaviors was detected, which lead to aggression among peers, classmates, disrespect for their peers, teachers, among other dissociating patterns such as : emergence of class standards, lack of attention, lack of respect, absence of good manners, issuance of negative comments towards your peers and guardians. The methodology used had a mixed descriptive and field-type approach, qualitative because it analyzed the origin of the problem and its effects, and quantitative because the study sample was selected by collecting information through statistically processed questionnaires which presented the results obtaine……………..